Antibody–drug conjugates: an emerging modality for the treatment of cancer. (August 2014) - Leal, Mauricio; Sapra, Puja; Hurvitz, Sara A.; Senter, Peter; Wahl, Alan; Schutten, Melissa; Shah, Dhaval K.; Haddish‐Berhane, Nahor; Kabbarah, Omar
Abstract : Antibody–drug conjugates (ADCs) offer promise as a therapeutic modality that can potentially reduce the toxicities and poor therapeutic indices caused by the lack of specificity of conventional anticancer therapies. ADCs combine the potency of cytotoxic agents with the target selectivity of antibodies by chemically linking a cytotoxic payload to an antibody, potentially creating a synthetic molecule that will deliver targeted antitumor therapy that is both safe and efficacious. The ADC repertoire contains a range of payload molecules, antibodies, and linkers. Two ADC molecules, Kadcyla® and Adcetris®, have been approved by the FDA, and many more are currently in clinical development.